RAGAM BAHASA DALAM KOMPONEN TUTUR - Trisnanurlita Herisetyanti; Henny Suharyati (Media Bahasa, Sastra, dan Budaya Wahana, 2019)
ABSTRACT The research goal is to analyze the use of languages and forms of speech components from the main characters in the Legend 2015 film by Brian Helgeland. A descriptive analysis approach is used to describe the usage of various languages. The main character conversations with others become the main source of data. The result shows that the intimate language most frequently used, yet the least is the variety of consultative language. Still, the form of speech components in each use of various languages is more influenced by the components of the participants, topics, functions, and settings. It is concluded that the usage of intimate languages is strongly influenced by the components of the participant's speech, both the topic, function, and background. Keywords: variety of languages, speech components, social context and Legend 2015 film